149k views
5 votes
Please help, I don't understand what I am doing wrong

Please help, I don't understand what I am doing wrong-example-1
User Mmseng
by
5.1k points

1 Answer

3 votes

\begin{gathered} f(x)=6x^2-x^3 \\ f^{^(\prime)}(x)=12x-3x^2 \\ f^{^{^(\prime)}}(1)=12(1)-3(1)^2 \\ f^{^(\prime)}(1)=12\text{ -3} \\ f^{^(\prime)}(1)=9 \\ y-y_{1\text{ }}=m(x-x_1) \\ m=f^{^(\prime)}(1) \\ y_1=\text{ 5} \\ x_1=1 \\ y\text{ -5 =}9(x\text{ -1)} \\ y\text{ = 5 +9x -9} \\ y=9x\text{ -}4 \end{gathered}

User Oherrala
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.